A Genome-Wide Identification of Osmotic Stress-Responsive MicroRNAs in Pyropia haitanensis (Bangiales, Rhodophyta) - Cao, Min; Wang, Dongmei; Kong, Fanna; Wang, Junhao; Xu, Kuipeng; Mao, Yunxiang (Frontiers in Marine Science, 2019)
Pyropia haitanensis, one of the most economically important marine crops worldwide, can recover from up to 80% water loss during emersion in the intertidal zone. However, little is currently known regarding the molecular mechanism involved in the response to osmotic stress at the post-transcriptional level. In this study, we profiled the transcriptional patterns of microRNAs (miRNAs) in P. haitanensis under the conditions of dehydration and succeeding rehydration. Forty-seven miRNAs were sequenced and characterized, which included 2 evolutionarily conserved and 45 novel miRNAs. Among these, 32 miRNAs were differentially expressed under osmotic stress conditions. The target genes were predicted to be related to catalytic activity, binding, transporter activity, transcription factor activity, signal transducer activity, and antioxidant activity. The miRNAPC-3p-99769_194 exhibited constant upregulation during dehydrated stress, whereas its target gene, a carbonic anhydrase, was downregulated as detected via qPCR. Furthermore, we identified genes that encode Dicer and Argonaute (AGO) proteins. The Dicer protein is encoded by two genes, each partially harboring several conserved domains. In this study, we discovered that there was a negative correlation in the miRNAPC-3p-99769_194 transcriptional pattern under osmotic stress, which revealed the essential role of miRNAs in the suppression of carbon fixation to maintain basic living conditions. Additionally, the Pyropia-specific organization of Dicer genes may be indicative of the distinctive structural features of miRNAs. This study provided novel insights into the miRNA-mediated regulatory mechanisms that are essential for desiccation-tolerance in P. haitanensis.